Need Analysis of Innovative Media Development Based on Local History of the Agung Temple in South Kalimantan - Nafi'ah, Ulfatun; Ayundasari, Lutfiah; Djoko Sulistyo, Wahyu (KnE Social Sciences, 2023)
This article aims to analyze the current needs of history learning since the introduction of the Independent Curriculum. Some of the latest needs that researchers get include, the renewal of materials and learning media. Following up on some of these needs, researchers present alternative solutions for history learning media with various appropriate technologies. Some of the appropriate technologies in question include 3D objects, 360 virtual media, augmented reality, and e-Books (OMAE). In the process of making and implementing it as an alternative solution, OMAE products are presented with content based on local history that is not Javacentric, namely the Agung Temple in South Kalimantan. In order to facilitate researchers in achieving these goals, qualitative research methods with an intrinsic case study approach was used as a basis for this research. The results obtained form this method, shows that OMAE products can be declared effective along with many benefits. In addition, with the presence of local history-based material content that is not Javacentric, it can make students wiser and able to maintain the harmonization of national and state life. Keywords: learning media, innovation, independent curriculum, Agung Temple